The Kangaroo and Emu Between Legal Worlds: Unsettling the Recognition of Difference - Rhys Aston; Kristopher Wilson (Law Text Culture, 2023)
This article examines the complex interplay between colonial legal systems and Indigenous laws, using the legal challenges faced by Arabunna Elder Kevin Buzzacott as a focal point. Buzzacott's 2004 conviction for the reclamation of a bronze Australian coat of arms, an act he deemed a fulfillment of his legal obligations under Arabunna Law, underscores the colonial legal system's refusal to acknowledge Aboriginal laws and ways of being. The authors argue that the colonial legal framework operates as a ‘nomocidal’ regime, perpetuating physical and conceptual violence against Indigenous peoples by asserting a singular legal authority that erases ontological difference. Through analysis of the Buzzacott case, the article further exposes the colonial legal system's preoccupation with Eurocentric notions of justice, which undermine Indigenous law-ways by eschewing engagement with ontological difference in favour of a universalist claim to authority. By exploring alternative legal worlds and ontologies, the authors advocate for a decolonial approach to justice that acknowledges and respects the multiplicity of legal realities. This shift requires a re-evaluation of the legal system to accommodate ontological pluralism, moving towards a more inclusive and just legal landscape that provides space for Indigenous laws and ways of being. The article is a tribute to Uncle Kevin Buzzacott, highlighting his struggle for recognition and justice as emblematic of the broader challenges faced by Indigenous peoples in colonial legal contexts.